Textured Asymmetric Membrane Electrode Assemblies of Piezoelectric Phosphorene and Ti3C2Tx MXene Heterostructures for Enhanced Electrochemical Stability and Kinetics in LIBs - Li, Yihui; Xie, Juan; Wang, Ruofei; Min, Shugang; Xu, Zewen; Ding, Yangjian; Su, Pengcheng; Zhang, Xingmin; Wei, Liyu; Li, Jing‑Feng; Chu, Zhaoqiang; Sun, Jingyu; et al. (Nano-Micro Letters, 2024)
Black phosphorus with a superior theoretical capacity (2596 mAh g−1) and high conductivity is regarded as one of the powerful candidates for lithium-ion battery (LIB) anode materials, whereas the severe volume expansion and sluggish kinetics still impede its applications in LIBs. By contrast, the exfoliated two-dimensional phosphorene owns negligible volume variation, and its intrinsic piezoelectricity is considered to be beneficial to the Li-ion transfer kinetics, while its positive influence has not been discussed yet. Herein, a phosphorene/MXene heterostructure-textured nanopiezocomposite is proposed with even phosphorene distribution and enhanced piezo-electrochemical coupling as an applicable free-standing asymmetric membrane electrode beyond the skin effect for enhanced Li-ion storage. The experimental and simulation analysis reveals that the embedded phosphorene nanosheets not only provide abundant active sites for Li-ions, but also endow the nanocomposite with favorable piezoelectricity, thus promoting the Li-ion transfer kinetics by generating the piezoelectric field serving as an extra accelerator. By waltzing with the MXene framework, the optimized electrode exhibits enhanced kinetics and stability, achieving stable cycling performances for 1,000 cycles at 2 A g−1, and delivering a high reversible capacity of 524 mAh g−1 at − 20 ℃, indicating the positive influence of the structural merits of self-assembled nanopiezocomposites on promoting stability and kinetics. Highlights: 1 An asymmetric membrane electrode based on phosphorene/MXene heterostructure-textured nanopiezocomposite was fabricated via a polar urea-assisted self-assembly strategy and additive manufacturing of the heterostructure beyond the skin effect. 2 The merits of this novel asymmetric heterostructure-textured electrode and its intrinsic piezoelectricity were detailedly discussed. 3 The stepwise lithiation process of phosphorene was revealed, and the enhanced electrochemical properties of this phosphorene-based nanopiezocomposite textured electrode were verified by the improved cycling stability and kinetics.